Correlation of the rates of solvolysis of α-bromoisobutyrophenone using both simple and extended forms of the Grunwald-Winstein equation and the application of correlation analysis to related studies - Kevill, Dennis Neil; Kim, Chang-Bae; D’Souza, Malcolm John (European Journal of Chemistry, 2018)
A Grunwald-Winstein treatment of the specific rates of solvolysis of α-bromoisobutyro phenone in 100% methanol and in several aqueous ethanol, methanol, acetone, 2,2,2-trifluoroethanol (TFE), and 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP) mixtures gives a good logarithmic correlation against a linear combination of NT (solvent nucleophilicity) and YBr (solvent ionizing power) values. The l and m sensitivity values are compared to those previously reported for α-bromoacetophenone and to those obtained from parallel treatments of literature specific rate values for the solvolyses of several tertiary mesylates containing a C(=O)R group attached at the α-carbon. Kinetic data obtained earlier by Pasto and Sevenair for the solvolyses of the same substrate in 75% aqueous ethanol (by weight) in the presence of silver perchlorate and perchloric acid are analysed using multiple regression analysis.